Glass ionomer heated or not to identify bone defect created in rat calvaria - Marcela Lucio CALDEIRA; Valéria Rodrigues FREITAS; José Ricardo SANTOS; Maria Júlia Giancursi ABONIZIO; Maria Fernanda do NASCIMENTO; Larissa Sgarbosa de Araújo MATUDA; Carolina dos Santos SANTINONI (Universidade Estadual Paulista, 2022)
Abstract Introduction Some experimental models have been used to evaluate the use of biomaterials in bone regeneration. Among them are the critical size defects (CSD) created in rat calvaria. An experimental model has been described in the literature, in which "L" markings are performed on the margins of the bone defects in order to assist in the precise identification of these defects during laboratory processing and analysis of the results. In the proposed model, the "L" markings are filled with amalgam. Objective The purpose of the present study was to evaluate the amalgam replacement of an experimental bony defect model in rat calvaria by heated or unheated glass ionomer. Material and method 24 rats were used. A 5 mm CSD was created at each animal calvaria. Two "L" shaped markings were made 2 mm from the margins of the bone defect, filled with amalgam (Group AM), heated glass ionomer cement (Group GIh) or not (Group GI). The animals were euthanized 15 days postoperatively. The areas of the surgical defect and the L-shaped marking were histomorphometrically analyzed and the data were analyzed statistically (p <0.05). Result There were no significant clinical, histological or methodological differences among the experimental groups. Conclusion It can be concluded that GI can replace AM in the proposed experimental model and GI heating did not promote additional benefits.